Systematic Review of Oral and Topical Botanicals in Reducing Photosensitivity - Suzana Saric, BA; Ashley K. Clark; Raja K. Sivamani (Dermatology, 2017)
Objectives: Various treatment options are available for the management of photosensitivity. The objective of this review is to evaluate the use of botanicals rich in antioxidants for photosensitivity reduction. Design: Embase and Ovid/MEDLINE databases were searched for clinical studies evaluating antioxidants from botanical sources in the management of photosensitivity. Results: Of 339 citations, 10 met the inclusion criteria. Four studies evaluated Polypodium leucotomos, two evaluated Camelia sinensis, while Hamamelis, Pistacia vera L., Citrus sinensis varieties Moro, Tarocco and Sanguinello, and Capparis spinosa were investigated in one study each. Five studies evaluated oral supplementation, four evaluated topical formulations, and one study evaluated both oral and topical antioxidants. Main results were summarized. Conclusions: There is some evidence that antioxidants derived from botanical sources may be beneficial in reducing skin erythema and photosensitivity. However, the studies included in this review have methodological limitations and large scale randomized, placebo controlled trials are needed to further evaluate the efficacy and safety of botanical antioxidants in photosensitivity reduction.